Central and Peripheral Mechanisms Underlying Physiological and Drug-Induced Fluctuations in Brain Oxygen in Freely-Moving Rats - Kiyatkin, Eugene A. (Frontiers in Integrative Neuroscience, 2018)
The goal of this work is to consider physiological fluctuations in brain oxygen levels and its changes induced by opioid drugs. This review paper presents, as a comprehensive story, the most important findings obtained in our laboratory by using high-speed amperometry with oxygen sensors in awake, freely moving rats; most of these findings were separately published elsewhere. First, we show that oxygen levels in the nucleus accumbens (NAc) phasically increase following exposure to natural arousing stimuli. Since accumbal neurons are excited by arousing stimuli and NAc oxygen levels increase following glutamate microinjections in the NAc, local neural activation with subsequent cerebral vasodilation appears to mediate the rapid oxygen increases induced by arousing stimuli. While it is established that intra-cerebral entry of oxygen depends on brain metabolism, physiological increases in NAc oxygen occurred more rapidly than increases in metabolic activity as assessed by intra-brain heat production. Therefore, due to neural activation and the subsequent rise in local cerebral blood flow, the brain receives more oxygen in advance of its metabolic requirement, thus preventing potential metabolic deficits. In contrast to arousing stimuli, three opioid drugs tested (heroin, fentanyl, and oxycodone) decrease oxygen levels. As confirmed by our recordings in the subcutaneous space, a densely vascularized location with no metabolic activity of its own, these decreases result from respiratory depression with subsequent fall in blood oxygen levels. While respiratory depression was evident for all tested drugs, heroin was ~6-fold more potent than oxycodone, and fentanyl was 10-20-fold more potent than heroin. Changes in brain oxygen induced by respiratory depression appear to be independent of local vascular and blood flow responses, which are triggered, via neuro-vascular coupling, by the neuronal effects of opioid drugs.